Assessment of heavy metal pollution in soils along major roadside areas in Botswana - K. B. Mmolawa; A. S. Likuku; G. K. Gaboutloeloe (African Journal of Environmental Economics and Management, 2020)
Assessment of heavy metal pollutants: Al, Co, Cu, Fe, Pb, Mn, Ni and Zn was conducted along major roadside soils of Botswana, lying between latitudes 18°S to 27°S and longitudes 20°E to 29°E using enrichment factor ratios (EF), contamination factor (CF), pollution load index (PLI) and geoaccumulation index (Igeo) methods. The studied sites were demarcated into five zones referred to as FN (Francistown-Nata), NM (Nata-Maun), MG (Maun-Ghanzi), GK (Ghanzi-Kang) and TS (Tshabong-Sekoma). All the four pollution assessment methods revealed that zones FN, NM and MG are pollution impacted as compared to GK and TS zones. Results of multivariate analysis suggest mixed origins of pollution sources including human activities, vehicular emissions and lithogenic occurrences. Al, Cu, Fe, Mn, Zn and Co is of mixed origins of pollutants, with Fe and Mn being predominantly lithogenic, and vehicular emissions characterised by Pb and Ni. The findings in this study will serve to create awareness of vehicular heavy metal pollution to Botswana policy makers in the mitigation of vehicular pollution, as it is barely monitored.